2017
DOI: 10.1039/c7ra05692c
|View full text |Cite
|
Sign up to set email alerts
|

Efficient photocatalytic oxidation of methane over β-Ga2O3/activated carbon composites

Abstract: Efficient photocatalytic oxidation of CH4 can be implemented over Ga2O3/AC composites, owing to the enhanced separation of photoinduced e−/h+ pairs and generation of active species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…Nanostructured semiconductors with high specific surface areas are generally applied as the photocatalysts for the oxidation of CH 4 . [17][18][19][20][21] Adjusting the band gap of semiconductors by doping, defect engineering,and fabricating hybrid semiconductors is beneficial for expanding the spectral range of the absorption. [22][23][24][25][26][27] In addition, morphology control and surface modification are also able to alter the range of light absorption.…”
Section: Absorption Unitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nanostructured semiconductors with high specific surface areas are generally applied as the photocatalysts for the oxidation of CH 4 . [17][18][19][20][21] Adjusting the band gap of semiconductors by doping, defect engineering,and fabricating hybrid semiconductors is beneficial for expanding the spectral range of the absorption. [22][23][24][25][26][27] In addition, morphology control and surface modification are also able to alter the range of light absorption.…”
Section: Absorption Unitsmentioning
confidence: 99%
“…In the photooxidation of CH 4 ,s emiconductor/semiconductor hybrids are commonly used. [20,21,26,35,38,48] Forexample, Li et al synthesized aC uO-loaded ZnO catalyst for the photocatalytic total oxidation of methane (TOM). [26] The loading of CuO with aband gap of 1.7 eV not only promotes the absorption of visible light but also slightly narrows the band gap of ZnO,thereby leading to ashift of the absorption edge of ZnO to al onger wavelength.…”
Section: Semiconductor/semiconductor Hybridmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, light intensity has a significant effect on methane oxidation in the PC system. Wei et al investigated the effect of light intensity on the photocatalytic performance of Ga 2 O 3 /AC composite for methane oxidation [48]. Wei et al reported that the oxidation of methane is directly proportional to the intensity of the irradiation, indicating that light plays a major role in CH 4 oxidation via PC system.…”
Section: Other Factors That Affect Methane Oxidationmentioning
confidence: 99%
“…This increase of activity was ascribed to a strong adsorption capacity and improved separations of photoelectrons ( e − ) and vacancies ( h + ) pairs. The authors consider this method promising to remove low concentrations of methane ( Wei et al, 2017 ).…”
Section: Heterogeneous Photocatalysts For Methane Conversionmentioning
confidence: 99%